Pemberdayaan Anak Berkebutuhan Khusus melalui Pelatihan Kewirausahaan Berbasis Kerajinan Purun di SKHN 1 Palangka Raya: Empowerment of Students with Special Needs through Purun-Based Handicraft Entrepreneurship Training at State Special School 1 Palangka Raya - Yovita, Yovita; Koesanto, Stefani Made Ayu Artharini; Sumiyati, Sri; Rahmaddian, Rahmaddian; Adiwijaya, Saputra; Raysharie, Puput Iswandyah; Suryanatha, Ida Bagus; Purbosari, Nita Ryan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service program aims to enhance the economic independence of Children with Special Needs (CSN) through entrepreneurship training based on purun handicrafts at the State Special School in Palangka Raya. The activity was carried out by a team from Universitas Terbuka in collaboration with the partner school to strengthen entrepreneurial skills, creativity, and digital financial management among CSN students and their teacher assistants. The implementation method employed a participatory approach, hands-on practice, and intensive mentoring, covering materials on business idea development, simple business planning, digital marketing, and financial literacy. The results showed significant improvements in four main areas: knowledge of local purun materials, creativity and weaving skills, entrepreneurial interest and attitude, and basic business understanding. Analysis of the pre-test and post-test demonstrated statistically significant differences (p <0.05) across all indicators. This program has made a tangible contribution to strengthening the local creative economy and promoting social empowerment for the disability community.